The Relationship Between Non-Audit Service and Auditor Independence with Evidence - Venkatesh; Aghajan, Abbas Pour (Indian Journal of Finance, 2008)
The significance of independence in the work of the independent auditor is so well established that little justification is needed to re-emphasize this concept as one of the corner- stones in any structure of auditing theory (Mautz et al, 1961). However, the force of globalization, complexity of business practice and assurance services created multi disciplines. These multidisciplinary firms offer audit and NAS to audit clients. From the recent scandal of failures and collapse in audit services all over the world, it is apparent that the joint provision of audit and NAS could raise the risk of client retention due to economic incentives and receiving lucrative NAS fee itself will cause a tendency to agree with clients. The authors believe this shortcoming and the existing scandals of companies have reduced the equity values by billion dollars. In short, they believe that practicing NAS by auditors leads to the re-emergency of agency theory defining and clarifying audit and NAS activities from audit services.